Radiologic Improvement After Early Medical Intervention in Localised Facial Morphea. Issue 2 (10th February 2016) - Khan, Muhammad Amjad; Shaw, Lindsay; Eleftheriou, Despina; Prabhakar, Prab; Chong, Wui K.; Glover, Mary
Abstract: We report the case of a young girl who presented with hemiparesis, seizures, and subtle features consistent with a linear form of facial morphea (en coup de sabre). She was treated with pulsed parenteral steroids and oral steroids and started on methotrexate. Magnetic resonance imaging results and neurologic problems improved after 6 months. Switching off inflammation early in the course of disease seemed to reverse some of the central nervous system changes. Assessment of children with unexplained hemiparesis and seizures should include careful examination of the face and scalp, looking for subtle signs of skin change and asymmetry. This is one of the few reported cases of neuroradiologic improvement after immunosuppressive treatment in a child with en coup de sabre.